2018
DOI: 10.1002/nbm.4039
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous B1+ for bilateral breast imaging at 7 T using a five dipole transmit array merged with a high density receive loop array

Abstract: To explore the use of five meandering dipole antennas in a multi‐transmit setup, combined with a high density receive array for breast imaging at 7 T for improved penetration depth and more homogeneous B 1 field. Five meandering dipole antennas and 30 receiver loops were positioned on two cups around the breasts. Finite difference time domain simulations were performed to evaluate RF safety limits of the transmit setup. Scattering parameters of the transmit setup and couplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…Note, however, that in case the true cause is not the assumed underestimation of ρ, over or under corrections can occur. Both correctable B1+ ranges are too narrow to reliably correct all data gathered with the current setup used in this study, but recent results suggest that they may be compatible with the degree of homogeneity that can be achieved with a novel bilateral transmit array …”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Note, however, that in case the true cause is not the assumed underestimation of ρ, over or under corrections can occur. Both correctable B1+ ranges are too narrow to reliably correct all data gathered with the current setup used in this study, but recent results suggest that they may be compatible with the degree of homogeneity that can be achieved with a novel bilateral transmit array …”
Section: Discussionmentioning
confidence: 58%
“…The most obvious solution may be to tackle the problem at the source: improve the homogeneity of the B1+ field. In recent years, progress has been made in the field of RF coil design toward that end . However, a completely homogeneous B1+ field is nontrivial to achieve even with state‐of‐the‐art hardware, so some amount of field inhomogeneity is always expected.…”
Section: Introductionmentioning
confidence: 99%
“…The B + 1 inhomogeneity was measured (with the detuned array in place) by taking the SD and dividing by the mean of the same region throughout the phantoms on both sides of the bilateral coil. 15,18 SNR comparisons between the array and the volume coil were performed on an axial slice through the center of the phantoms by taking the average and maximum signal values throughout both phantoms and dividing by the SD of the noise in the noise-only image then scaling by a factor of 0.655. 32 SNR maps were generated for each image by dividing the signal intensity by the SD of a selected region in the noise-only image on a pixel-by-pixel basis.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] Several studies have reported the benefits of high-field (7T) imaging in DCE and DWI studies, [11][12][13][14] where the use of array coils is particularly beneficial to increase the achievable temporal resolution. [15][16][17][18] The challenges of high-field imaging with respect to homogeneous RF excitation and specific absorption rate are well-documented. 19,20 Our group has previously reported on the forced current excitation (FCE) technique as a way to transmit effectively at 7T, achieving homogeneous excitation in the presence of the asymmetric load presented by the patient in a prone position, while remaining within specific absorption rate regulations.…”
Section: Introductionmentioning
confidence: 99%
“…Using eight independent RF power amplifiers (RFPAs) in pTX mode allows driving the individual 8Tx channels of the array dynamically (i.e. to vary the magnitude/phase of each channel or the RF-pulse waveforms), which enables shaping of 2D and 3D excitation profiles based on a wide-range of optimization criteria 51,52 . Another major issue is that the limited RF power given from the RFPA is distributed to both array parts.…”
mentioning
confidence: 99%